2008
DOI: 10.1007/s00213-008-1121-z
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of AMPA receptors produces anxiolytic-like behavior in rodents: Effects of GYKI 52466 and its novel analogues

Abstract: The results show that non-competitive AMPA receptor antagonists can profoundly block anxiety-like behavior in rodents independently from their motor depressant activity. However, the sedative properties at higher doses might limit their therapeutic utility as new anxiolytic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Anxiety-like states in rodents have been coupled to increased AMPAR-mediated neurotransmission in the basolateral amygdala (Christian et al, 2012;Läck et al 2007) as well as increased levels of GluA1 in the cortex and hippocampus (Izzo et al, 2001;Xiang et al, 2011). In line with these findings, rat studies have reported anxiolytic effects of AMPA/kainate receptor antagonism in the elevated plus maze (EPM) and shock-based conflict tests (Alt et al, 2006;Kapus et al 2008;Kotlinska and Liljequist, 1998). In mice, the competitive AMPAR antagonist CNQX showed anxiolytic-like effects in the EPM test and decreased latency to eat in the novelty-induced hypophagia (NIH) test, indicative of an anxiolytic-like response (Bi et al, 2013).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Anxiety-like states in rodents have been coupled to increased AMPAR-mediated neurotransmission in the basolateral amygdala (Christian et al, 2012;Läck et al 2007) as well as increased levels of GluA1 in the cortex and hippocampus (Izzo et al, 2001;Xiang et al, 2011). In line with these findings, rat studies have reported anxiolytic effects of AMPA/kainate receptor antagonism in the elevated plus maze (EPM) and shock-based conflict tests (Alt et al, 2006;Kapus et al 2008;Kotlinska and Liljequist, 1998). In mice, the competitive AMPAR antagonist CNQX showed anxiolytic-like effects in the EPM test and decreased latency to eat in the novelty-induced hypophagia (NIH) test, indicative of an anxiolytic-like response (Bi et al, 2013).…”
Section: Introductionmentioning
confidence: 81%
“…In mice, the competitive AMPAR antagonist CNQX showed anxiolytic-like effects in the EPM test and decreased latency to eat in the novelty-induced hypophagia (NIH) test, indicative of an anxiolytic-like response (Bi et al, 2013). However, in a comprehensive study by Kapus et al (2008), testing six different AMPAR antagonists in rat and mouse anxiety tests, only one of the AMPAR antagonists (EGIS-8332) showed anxiolytic-like effects in mice, as revealed by the mouse light/dark test (Kapus et al, 2008). AMPAR antagonism has also shown anxiogenic-like effects in the mouse EPM test (Karcz-Kubicha and Liljequist, 1995), and the AMPAR potentiator CX546 reduced anxiety-related behaviour in the mouse marble burying (MB) test (Iijima et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, the anxiolitic effects of CNQX in EPM and different expression levels of GluR1 and GluR2 mRNAs in these neurobiological conditions strengthen the AMPAergic system as a crucial therapeutic target for the treatment of anxiety (Kapus et al 2008;Pittenger and Duman 2008) as well as proposing AMPA antagonists as neuroprotectors against anxiety-and depressive-related pathologies (Nakache et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Administration of drugs selectively targeting AMPARs, such as GYKI 52466 or LY32635, have been found to cause anxiolytic-like (Alt et al 2006;Kapus et al 2008;Kotlinska and Liljequist 1998;Matheus and Guimarães 1997), anxiogenic-like (Vekovischeva et al n.d.), or no changes (Fitzgerald et al 2010;Kapus et al 2008) in anxiety-related behaviors, depending on the rodent species tested or behavioral paradigm used. Mice lacking key phosphorylation sites on the AMPA subunit GluA1 also demonstrate decreases in anxiety (Kiselycznyk et al 2013).…”
Section: Therapies Targeting Postsynaptic Glutamatergic Receptorsmentioning
confidence: 96%